Flexural performance of steel-concrete-steel sandwich beams with lightweight fiber-reinforced concrete and corrugated-strip connectors: Experimental tests and numerical modeling - Hamed Roshani; Mehdi Yousefi; Nima Gharaei-Moghaddam; Seyed Hashem Khatibi (Case Studies in Construction Materials, 2023)
The present paper experimentally investigates the flexural behavior of steel-concrete-steel (SCS) composite beams with lightweight polypropylene fiber-reinforced concrete core and corrugated-strip shear connectors. For this purpose, the four-point bending tests have been performed on 11 specimens. This aims to investigate the influence of lightweight concrete core on the performance of the beams, and therefore all the parameters in the tested beams are kept constant except the type of concrete core. Based on the results of the performed quasi-static loading tests, the observed failure modes and force-displacement curves are reported and analyzed to achieve a deeper understanding of the influence of lightweight fiber-reinforced concrete on the flexural behavior of SCS beams. It was found that the utilization of polypropylene fiber has an improving influence on the performance of SCS beams, and especially enhances their toughness and ultimate deflection. A positive linear relationship between the fiber content (up to 2 %) with the specimen’s toughness was detected. It was also found that the addition of micro-silica to the lightweight fiber-reinforced concrete core results in considerable improvement in the flexural load capacity of the tested SCS beams. In addition, numerical finite element models including detailed material and geometric modeling of SCS beams are developed using the general software package ABAQUS. The accuracy of the developed models is validated using the attained experimental results. The numerical models can be used to simulate the load-deflection behavior and ultimate strength of SCS sandwich beams.